2010
DOI: 10.1016/j.jhep.2010.01.015
|View full text |Cite
|
Sign up to set email alerts
|

IGF activation in a molecular subclass of hepatocellular carcinoma and pre-clinical efficacy of IGF-1R blockage

Abstract: Background/Aims IGF signaling has a relevant role in a variety of human malignancies. We analyzed the underlying molecular mechanisms of IGF signaling activation in early hepatocellular carcinoma (HCC; BCLC class 0 or A) and assessed novel targeted therapies blocking this pathway Methods An integrative molecular dissection of the axis was conducted in a cohort of 104 HCCs analyzing gene and miRNA expression, structural aberrations and protein activation. The therapeutic potential of a selective IGF-1R inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
174
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 36 publications
9
174
0
2
Order By: Relevance
“…Our preclinical studies have identified measurable pharmacodynamic endpoints such as serum IGF bioactivity that will be useful for defining the pharmacokinetic/pharmacodynamic (PK/PD) relationship in humans. With regards to rational rather than arbitrary drug combinations, our findings indicate that coadministration of BI 836845 with rapalogs deserves consideration, and with respect to potential selection criteria for tumors that may be particularly responsive, autocrine expression of IGF-I or IGF-II may define a subpopulation of interest (52).…”
Section: Discussionmentioning
confidence: 95%
“…Our preclinical studies have identified measurable pharmacodynamic endpoints such as serum IGF bioactivity that will be useful for defining the pharmacokinetic/pharmacodynamic (PK/PD) relationship in humans. With regards to rational rather than arbitrary drug combinations, our findings indicate that coadministration of BI 836845 with rapalogs deserves consideration, and with respect to potential selection criteria for tumors that may be particularly responsive, autocrine expression of IGF-I or IGF-II may define a subpopulation of interest (52).…”
Section: Discussionmentioning
confidence: 95%
“…In vitro studies showed that abrogation of IGF1R activation and downstream signaling by the monoclonal antibody A12 significantly decreased cell viability and proliferation 1414. Although several IGF1R inhibitors or blocking antibodies have been tested in preclinical models or clinical trials for patients with HCC,9, 14, 15, 16 none has been approved by the FDA, possibly because inhibition of IGF1R alone may not be sufficient to effectively inhibit HCC cell growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , A12 delayed tumor growth and prolonged survival, reducing proliferation rates and inducing apoptosis 14. Although several IGF1R inhibitors or blocking antibodies have been tested in preclinical models or clinical trials for patients with HCC,9, 14, 15, 16 none has been approved by the FDA, possibly because inhibition of IGF1R alone may not be sufficient to effectively inhibit HCC cell growth and survival. Our data support this hypothesis as inhibition of IGF1R by shRNA or ceritinib has only a modest suppression on HCC proliferation and survival (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reduced expression of IGFBP-3 associated with promoter hypermethylation has been reported in human HCC samples (21). A recent study found aberrant activation of IGF1R in 21% of early stage hepatitis C-related HCC xases, and provided preclinical evidence of antineoplastic activity following IGF1R selective blockade using a monoclonal antibody (22). The potential role of the HBx viral protein as an inducer of IGF-IR expression has also been suggested (23).…”
Section: Discussionmentioning
confidence: 99%